ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN (STUDI KASUS PADA PT. SEPATU BATA TBK PERIODE TAHUN 2011 – 2013) - Manullang, Asna (Jurnal Ilmiah Binaniaga, 2013)
The company's ability to generate profits is the key to the success of the company can be said to have a good performance, because profit is a component of financial statements that are used as a tool to assess whether or not the performance of the company. ompanies need to analyze the financial statements for the financial statements used to assess the performance of the company, and is used to compare the condition of the company from the previous year to the current year, if the company is increasing or not so that companies consider the decision to be taken for the coming year in accordance with the company's performance , Performance is something to be achieved by someone. So the performance of the company is critical of the review process by the financial company to provide solutions in making an appropriate decision in a given period.Current ratio of the company in 2011-2013 respectively amounted to 212.76%, 212.38% and 169.26% indicates the company has performed well because the company has the ability to pay off its debts. Quick ratio of the company in 2011-2013, respectively for 82.4%, 80.5% and 59.9% indicates the company has performed less well as obligations of the company is greater than the liquid assets of the company. Cash ratio companies in 2011-2013 respectively amounted to 7.81%, 5.61% and 1.27% showed ilikuid company, the ratio shows the company's performance is not good because current liabilities greater than the company's cash. Based on the analysis of liquidity ratio Pt. Shoes Bata Tbk for three years can be said to be less good, it is due to the financial situation of the company showing the amount of debt the company is greater than the amount of assets owned. The conditions resulted in the value of the liquidity ratio in 2013 is low. Key word: rasio analysis; performance